2023
DOI: 10.3390/md21010040
|View full text |Cite
|
Sign up to set email alerts
|

A Concise Review on the Potential Applications of Rugulopteryx okamurae Macroalgae

Abstract: The brown macroalgae of the species Rugulopteryx okamurae has reached European waters and the Strait of Gibraltar as an invasive species. The proliferation and colonization of the species in subtidal and intertidal zones of these regions imposes significant threats to local ecosystems and additionally represents a significant socioeconomic burden related to the large amounts of biomass accumulated as waste. As a way to minimize the effects caused by the accumulation of algae biomass, investigations have been m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…The use of anti‐fouling materials (Fernandes et al, 2016) and the appropriate cleaning of the hull in dry‐dock with water treatment or by underwater technology that eliminates the fouling organisms, such as techniques using laser or ultrasound (Song & Cui, 2020), should also be required as part of renewable operating licenses, including recreational boating. Likewise, changes in and enforcement of legislation concerning the transportation of live organisms for feed, aquarium trade and management of aquaculture waste are also a concern (Barcellos et al, 2023; Lehtiniemi et al, 2015). Geographic areas with a higher risk of invasion need to be identified with environmental models based on changes in both climate and uses of the maritime space over time, driven by climate factors and new technology developments (Sánchez‐Velásquez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The use of anti‐fouling materials (Fernandes et al, 2016) and the appropriate cleaning of the hull in dry‐dock with water treatment or by underwater technology that eliminates the fouling organisms, such as techniques using laser or ultrasound (Song & Cui, 2020), should also be required as part of renewable operating licenses, including recreational boating. Likewise, changes in and enforcement of legislation concerning the transportation of live organisms for feed, aquarium trade and management of aquaculture waste are also a concern (Barcellos et al, 2023; Lehtiniemi et al, 2015). Geographic areas with a higher risk of invasion need to be identified with environmental models based on changes in both climate and uses of the maritime space over time, driven by climate factors and new technology developments (Sánchez‐Velásquez et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Control and eradication measures for marine macroalgal invasive species are mainly based on manual removal of vegetative (Barcellos et al, 2023) or reproductive thalli (Zanolla et al, 2018). Additionally, hyaline shock, smothering with sand or tarp cover, and herbicides such as copper sulphide or chlorine have been used with different levels of success to eliminate algal populations in stages of development, namely on large infested areas, large isolated patches and dispersed small patches (Cardigos et al, 2015).…”
Section: Management Considerationsmentioning
confidence: 99%
“…Recently, a phytochemical study identified the compound dilkamural, which may be responsible for the deterrence and toxic effect of macroalgae against herbivores [37]. On the other hand, R. okamurae is highly toxic due to its high concentration of sesquiterpenes, which are not present in other algae [38]. Likewise, the high terpene content of these algae, which constitutes the largest fraction of their volatile organic compound (VOC) content, makes their degradation difficult [39].…”
Section: Introductionmentioning
confidence: 99%
“…Tons of R. okamurae algal biomass are collected every year from the Spanish Mediterranean coastline [3], resulting in high costs for municipalities and several environmental problems [4,5]. In addition to the importance of mapping and controlling the expansion of the invasive seaweeds, to alleviate the economic costs derived from their recollection and disposal, the analysis of the potential applications of algae is a useful approach [2,6]. With this purpose, different authors have evaluated the use of the algae R. okamurae for the generation of biogas [7], as an ingredient of aquafeeds for fish farms [8], as a raw material for the development of bioplastics [9], or in composting processes [2].…”
Section: Introductionmentioning
confidence: 99%